2023
DOI: 10.1590/s2237-96222023000100007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and epidemiological characterization of suicides in the Chapecó micro-region, Santa Catarina, Brazil: an ecological study, 1996-2018

Abstract: Objetivo: identificar conglomerados espaciais do suicídio e características epidemiológicas na microrregião de Chapecó, SC, Brasil, 1996-2018. Métodos: estudo ecológico exploratório, com dados do Sistema de Informações sobre Mortalidade; foram calculadas taxas específicas de suicídio, e riscos relativos (RR) com intervalo de confiança de 95% (IC95%); na análise espacial, utilizou-se estatística scan. Resultados: 1.034 suicídios (13,7/100 mil habitantes), à razão homem/mulher de 3,79; a idade ≥ 60 anos apresent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…P-score quality depends on the accuracy of the available data. 30 However, it is important to stress the continuous updating…”
Section: Discussionmentioning
confidence: 99%
“…P-score quality depends on the accuracy of the available data. 30 However, it is important to stress the continuous updating…”
Section: Discussionmentioning
confidence: 99%
“…An extreme indicator of mental suffering, suicide, was assessed using data from the Mortality Information System for the period 1996-2018 and found higher risk among male and the elderly in Chapecó/ SC, as well as identifying geographical regions at greater risk based on spatial analysis. 5 A cohort based on High Complexity Procedure Authorizations for the period 2008-2017, found that off-label use of atypical antipsychotic medications in children and adolescents was frequent among health service users seen by the Specialized Pharmaceutical Care Component of the SUS. 6 A point common to the studies mentioned above was that data generated within the SUS were the source of these original articles.…”
Section: Mental Suffering and The Brazilian National Health Systemmentioning
confidence: 99%
“…6 A point common to the studies mentioned above was that data generated within the SUS were the source of these original articles. Four of these studies were based on systems comprised of data input by health service workers and managers, [3][4][5][6] highlighting the role of the SUS in providing information that is the basis for research that provides feedback to the health system and society, in addition to providing comprehensive and universal care in its widespread network. The recording of and access to information originated in the various activities of the SUS, and its improvement through indicator analysis, must be recognized and encouraged throughout society, especially by the scientific community.…”
Section: Mental Suffering and The Brazilian National Health Systemmentioning
confidence: 99%